A Case of Uncommon Quadricuspid Aortic Valve Stenosis Associated With Noonan Syndrome and Acromegaly - Chie Bujo; Kensuke Tsushima; Kan Nawata; Ryo Inuzuka; Aya Shinozaki-Ushiku; Genri Numata; Norifumi Takeda; Masaru Hatano; Hiroyuki Morita; Minoru Ono; Issei Komuro (Annals of Internal Medicine: Clinical Cases)
Quadricuspid aortic valve (QAV) is a congenital aortic valve malformation usually associated with aortic regurgitation. We encountered a patient with Noonan syndrome (NS) who had severe QAV stenosis caused by degenerative aortic cusps with an unprecedented spherical cyst-like morphology. The patient had also developed adult-onset acromegaly and an elevated serum growth hormone (GH) level that might have caused myxomatous degeneration of the congenital QAV. Although recombinant human GH has been used extensively in NS patients with short stature, this patient's case suggests that it is reasonable to monitor valvular degeneration as a possible outcome of GH action and cardiac hypertrophy.